3+-2x=-1.5x

Simple and best practice solution for 3+-2x=-1.5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3+-2x=-1.5x equation:


Simplifying
3 + -2x = -1.5x

Solving
3 + -2x = -1.5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '1.5x' to each side of the equation.
3 + -2x + 1.5x = -1.5x + 1.5x

Combine like terms: -2x + 1.5x = -0.5x
3 + -0.5x = -1.5x + 1.5x

Combine like terms: -1.5x + 1.5x = 0.0
3 + -0.5x = 0.0

Add '-3' to each side of the equation.
3 + -3 + -0.5x = 0.0 + -3

Combine like terms: 3 + -3 = 0
0 + -0.5x = 0.0 + -3
-0.5x = 0.0 + -3

Combine like terms: 0.0 + -3 = -3
-0.5x = -3

Divide each side by '-0.5'.
x = 6

Simplifying
x = 6

See similar equations:

| -(6+5a)-a=6 | | x^2-100=-21x | | 1x^2-19x=-47 | | 3(x+2)=72 | | 0.7y=1.3x+8 | | -2+5x=8(3x-5) | | -12-6y-8x=0 | | -5(-6y-7)-3y=8 | | x+23.25=50.75 | | 3j^2+66j+21=0 | | 14x^7y^2+2xy= | | x-23.25=50.75 | | 1d^2+30d+7=0 | | n+42=65 | | 4x-15=3x+7 | | 3+3.7b=10.3b+10 | | -2g^2-50g=18 | | 1p^2+24p=43 | | 12+z=567 | | 6(2.5x+1.5)+7.5(4x+5)= | | 9-55n+1=15 | | 40+8n=6(n+7) | | -4f^2+28f-20=0 | | -5x-3y=8 | | -5+4+h=23 | | 11a-10a-20=19 | | 3(4-8k)-1=-61 | | 40q^2-40q-30=0 | | 1/4h-8= | | 37+x=-2(1-7x) | | 3x+7y=176 | | -4k-44k=36 |

Equations solver categories